Implementación De Videojuegos Serios Para La Estimulación Cognitiva A Través De Una Página Web (2023)
The human brain is responsible for controlling all the activities of the body and the essential mental processes to carry out our daily activities, these processes are called cognitive functions, when the agility of these functions begins to be lost at an early stage, the cognitive deterioration (GrupFisioderm, 2023). Said deterioration can be caused by factors such as age, genetics, chronic diseases, among others, and has symptoms such as frequent forgetfulness, loss of train of thought, and difficulty in decision-making. If these are not foreseen, they can present irreversible pathologies. Finally, before they happen, the patient must slow down the deterioration of their cognitive functions, there are several methods to achieve this, among which is cognitive stimulation. Therefore, this project focuses on the creation of a web platform with different video games to achieve cognitive stimulation, these games are cataloged in the main areas of affection, such as memory, orientation, vision-perception, calculation capacity and Abstract thinking. developed through the Unity platform. In addition to the games, an informative Test based on tests such as "MoCA" and "Stroop" is presented on the website, with which the user is informed whether or not they can present signs of cognitive impairment. Both the games and the test are validated and tested by people with cognitive impairment, people without cognitive impairment, child neuropsychologists, and managers focused on educating children and adolescents with different levels of cognitive emotions.